Fortaleza de afetos: imagens e narrativas de uma cidade entre muros - Silva, Lara Denise Oliveira (2021)
According to most books, treatises, and anthropological manuals (CLIFFORD; MARCUS, 1986), ethnographic practice mainly requires, among other requirements, time shared with interlocutors and other "informants", readings and journaling of the situations experienced. When the field is a familiar space and time, an in differentiation between work and everyday life seems to mark the researcher's trajectory. The text presented below seeks to discuss the possibilities that arise from this characteristic of urban research and is committed to relations with the city that go beyond its materiality. From walks and encounters with inscriptions, risks, phrases, or words, mostly engraved with spray paint on the surfaces of the paths traveled in the daily life of the researcher in Fortaleza-CE, a questionnaire was given as to how intimate and how emotions can be felt. manifest in the public sphere. For research, the recurrence of words and phrases that seemed to escape the classifications of Street Art fantasies and made it possible to read emotions and intimacies between the lines of the street drew attention. Among the abundance of examples that have been cataloged in the last four years, I quote: wish, leave, joy, encouragement, December has mango. If a city can narrate about itself from the images that populate its surfaces, what are these contaminated visual enunciations of Fortaleza? These and other questions mobilized the research and more than the impetus to decipher them, this text seeks to narrate encounters with public and urban words and images, in addition to resorting to ambulation (CERTEAU, 1994) as a research method. Therefore, it is believed that from these narratives, Fortaleza can make itself known not from above or from above, but from the street floor, from the perspective of what the city does (AGIER, 2011).